The Protective Role Of Spirulina On Doxorubicin Induced Genotoxicity In Germ Cells Of Rats - M.SUDHA; S.KAVIMANI (International Journal of Pharma and Bio Sciences, 2011)
Doxorubicin is a potent antitumor agent used against many cancers. It has genotoxic effect on human non-tumor (normal) cells. Hence, it is very important to reduce its toxicity to the normal cells. This goal can be achieved by concurrent administration of free radical scavenging agents, like antioxidants. In the present study, adult male albino rats of Wistar strain are administered with Doxorubicin (3 mg/kg body weight, intraperitonially), once in a week for 35 days and Spirulina (250 mg/kg body weight, oral) daily prior to Doxorubicin administration. Doxorubicin treated rats showed a significant decrease in sperm count and increase in the sperm head abnormalities. However, the combined treatment of Spirulina with doxorubicin restores the sperm count and decreases the incidence of sperms with head abnormalities. This study indicates that administration of Spirulina prior to Doxorubicin might prevent the germ cell toxicity in male rats.